Pathogenesis and Function of Interleukin-35 in Rheumatoid Arthritis - Xin, Pan Lin; Jie, Li Fan; Cheng, Qian; Bin, Du Yi; Dan, Cheng Wen (Frontiers in Pharmacology, 2021)
It is well known that RA (Rheumatoid arthritis) is an autoimmune disease characterized by multiple and symmetric arthropathy. The main pathological features of RA are synovial hyperplasia, angiogenesis, pannus formation, inflammatory cell infiltration, articular cartilage, bone destruction, and ultimately joint dysfunction, even deformity. IL-35 (Interleukin-35) is a new member of the IL-12 (Interleukin-12) family, which is an immunosuppressive and anti-inflammatory cytokine secreted mainly by Treg (T regulatory cells). There is evidence suggested that IL-35 can attenuate the progression of RA through influencing the immune and pathological process. It suggests that IL-35 played an important role in the pathogenesis of RA, and can be used as a potential target for the future treatment of RA. This review summarizes the recent advances of IL-35 in the pathological roles and the therapeutic potential roles in RA.